PENERAPAN METODE FUZZY TOPSIS DALAM PENGAMBILAN KEPUTUSAN PEMILIHAN BRAND PRODUK AIR MINERAL - Minanda, Febriyan Biopsa; Romli, Moh Ali (Jurnal Informatika Teknologi dan Sains (Jinteks), 2024)
Water is a fundamental human necessity. According to the Susenas by BPS in March 2023, 40.64% of people primarily consume mineral water, with usage increasing by 1.24% annually, leading to concerns about the availability of safe drinking water. The United States Environmental Protection Agency (EPA) sets the safe pH range for water between 6.5 and 8.5, while both the World Health Organization (WHO) and the Indonesian Ministry of Health (Permenkes) recommend a TDS level of 300-500 mg/liter. Consumers often face difficulty choosing among various mineral water brands due to conflicting claims about quality, packaging, and price. To address this issue, a Decision Support System (DSS) was developed using the Fuzzy TOPSIS method, focusing on pH and TDS as the primary parameters. The results show that Alfa, Aqua, and Club rank highest, each with a preference value of 1, while Pristine ranks the lowest at 0.327. From the results obtained, Alfa, Aqua, and Club products can increase their stock production because these products are the right choice for consumers.